NEW CONSTITUTIONAL REFORMS AND THE “UZBEKISTAN – 2030” MODEL: INTERCONNECTED RELATIONSHIPS (Modern American Journal of Social Sciences and Humanities, 2026)
This article provides an in-depth analysis of the logical interconnection and systemic nature between the updated Constitution of the Republic of Uzbekistan and the “Uzbekistan – 2030” strategy. Constitutional reforms are interpreted not merely as an update of a legal document, but as a strategic foundation that defines the country’s long-term development model. The main focus of the article is to reveal the extent to which the principles of a “social state,” “human dignity,” “rule of law,” and “secular state,” enshrined in the new version of the Basic Law, are aligned with the priority goals of the “Uzbekistan – 2030” strategy. The study thoroughly examines issues related to the development of human capital, particularly guarantees of access to quality education and healthcare services, economic freedoms, and the legal protection of business entities. In addition, the article presents a comparative analysis of the constitutional foundations of environmental sustainability and the transition to a “green economy” in relation to strategic objectives. Within this analysis, the Constitution is interpreted as a legal roadmap for societal development, while the Strategy is viewed as a practical mechanism for achieving the goals outlined in that roadmap. The central idea of the article is that the new constitutional norms serve not only as a legal basis for the successful implementation of the “Uzbekistan – 2030” model, but also as a key guarantee of sustainable development. The study concludes with practical recommendations and findings aimed at fully harmonizing national legislation with the updated Constitution and the objectives of the Strategy, enhancing the accountability of state bodies, and strengthening Uzbekistan’s position in international rankings. This work is intended for legal scholars, students, and the general public, and contributes to a deeper understanding of the essence of ongoing reforms in the country.